The Tennessee Medicaid medication therapy management program: early stage contextual factors and implementation outcomes - Kenneth C. Hohmeier; Chelsea Renfro; Kea Turner; Parin Patel; Estrella Ndrianasy; Renee Williams-Clark; Lora Underwood; Justin Gatwood (BMC, 2021)
Abstract Background First investigated in the 1990s, medication therapy management (MTM) is an evidence-based practice offered by pharmacists to ensure a patient's medication regimen is individualized to include the safest and most effective medications. MTM has been shown to a) improve quality of patient care, b) reduces health care costs, and c) lead to fewer medication-related adverse effects. However, there has been limited testing of evidence-based, a-priori implementation strategies that support MTM implementation on a large scale. Methods The study has two objectives assessed at the organizational and individual level: 1) to determine the adoption, feasibility, acceptability and appropriateness of a multi-faceted implementation strategy to support the MTM pilot program in Tennessee; and 2) to report on the contextual factors associated with program implementation based on the Consolidated Framework for Implementation Research (CFIR). The overall design of the study was a hybrid type 2 effectiveness-implementation study reporting outcomes of Tennessee state Medicaid's (TennCare) MTM Pilot program. This paper presents early stage implementation outcomes (e.g., adoption, feasibility, acceptability, appropriateness) and explores implementation barriers and facilitators using the CFIR. The study was assessed at the (a) organizational and (b) individual level. A mixed-methods approach was used including surveys, claims data, and semi-structured interviews. Interview data underwent initial, rapid qualitative analysis to provide real time feedback to TennCare leadership on project barriers and facilitators. Results The total reach of the program from July 2018 through June 2020 was 2033 MTM sessions provided by 17 Medicaid credentialed pharmacists. Preliminary findings suggest participants agreed that MTM was acceptable (μ = 16.22, SD = 0.28), appropriate (μ = 15.33, SD = 0.03), and feasible (μ = 14.72, SD = 0.46). Each of the scales had an excellent level of internal (> 0.70) consistency (feasibility, α = 0.91; acceptability, α = 0.96; appropriateness, α = 0.98;). Eight program participants were interviewed and were mapped to the following CFIR constructs: Process, Characteristics of Individuals, Intervention Characteristics, and Inner Setting. Rapid data analysis of the contextual inquiry allowed TennCare to alter initial implementation strategies during project rollout. Conclusion The early stage implementation of a multi-faceted implementation strategy to support delivery of Tennessee Medicaid's MTM program was found to be well accepted and appropriate across multiple stakeholders including providers, administrators, and pharmacists. However, as the early stage of implementation progressed, barriers related to relative priority, characteristics of the intervention (e.g., complexity), and workflow impeded adoption. Programmatic changes to the MTM Pilot based on early stage contextual analysis and implementation outcomes had a positive impact on adoption.